In vivo phenotypic and molecular characterization of retinal degeneration in mouse models of three ciliopathies. (September 2019) - Brun, Agnès; Yu, Xiangxiang; Obringer, Cathy; Ajoy, Daniel; Haser, Elodie; Stoetzel, Corinne; Roux, Michel J.; Messaddeq, Nadia; Dollfus, Hélène; Marion, Vincent
Abstract: Cilia are highly conserved and ubiquitously expressed organelles. Ciliary defects of genetic origins lead to ciliopathies, in which retinal degeneration (RD) is one cardinal clinical feature. In order to efficiently find and design new therapeutic strategies the underlying mechanism of retinal degeneration of three murine model was compared. The rodent models correspond to three emblematic ciliopathies, namely: Bardet-Biedl Syndrome (BBS), Alström Syndrome (ALMS) and CEP290-mediated Leber Congenital Amaurosis (LCA). Scotopic rodent electroretinography (ERG) was used to test the retinal function of mice, Transmitted Electron microscopy (T.E.M) was performed to assess retinal structural defects and real-time PCR for targeted genes was used to monitor the expression levels of the major apoptotic Caspase-related pathways in retinal extracts to identify pathological pathways driving the RD in order to identify potential therapeutic targets. We found that BBS and CEP290-mediated LCA mouse models exhibit perinatal retinal degeneration associated with rhodopsin mislocalization in the photoreceptor and the induction of an Endoplasmic Reticulum (ER) stress. On the other hand, the tested ALMS mouse model, displayed a slower degeneration phenotype, with no Rhodopsin mislocalization nor ER-stress activity. Our data points out that behind the general phenotype of vision loss associated with these ciliopathies, the mechanisms and kinetics of disease progression are different. Highlights: Different mouse models for RP associated ciliopathies are compared. Ciliopathies models, Bbs1, Bbs10, and the Cep290 -mediated Leber congenital amaurosis model showed an increased of UPR. Alström syndrome model namely Alms foz/foz showed no induction in the UPR response. Identifying common mechanisms underlying Retinitis pigmentosa might provide new therapeutics avenue for this pathology.